Epidemiology Of Canine Pyometra In Gujarat - Gupta, A.K.; Dhami , A.J.; Patil , D.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
This epidemiological investigation was taken up on 17 bitches, 9 pyometric (6 open; 3 closed pyometra) and 8 normal bitches presented for ovario-hysterectomy at the College Clinic. The age range of affected bitches was 2 to 13 years with a mean of 7.61 ± 1.31 years. The age of normal bitches presented for spaying ranged from 1.5 to 4.5 years with a mean of 3.31 ± 0.33 years. Of the 9 pyometric bitches, 4 cases (44.44 %;) were in 9-12 years age group followed by 3 cases (33.33 %) in 13 years age group. Further, the highest incidence of pyometra was observed in Pomeranian breed (4 cases) and in nulliparous bitches (77.78 %). Oestrous cycle was irregular in 44.44 and 62.50 per cent of pyometric and normal bitches. None of the bitches had received exogenous steroid- estrogen or progesterone.
Keywords: Bitch; Epidemiology; Pyometra; Spaying